The Design of a Plastic Shredder Machine with The Crusher Cutting Knife Model for Environmentally Sustainable - Putra Adjie Suwignyo; Rahmadi Kusumastuti; Amir; Dodi Mulyadi; Khoirudin (Jurnal Teknik Mesin Mechanical Xplore, 2023)
Indonesia produced about 31.2 million metric tons of garbage in 2021. Roughly 87.1% of the total waste is comprised-evaluated of plastic waste. Plastic waste takes a very long time to break down in the environment. It took decades for trash made of plastic to decompose. Disorganized waste management at the landfill is a significant source of plastics-related problems. In order to reuse plastic garbage, it must be crushed up first before the recycling process. The primary objective of the design process for the crushing plastic machine used to shred plastic waste was to maximize productivity. The design of the machine that crushes plastic waste was created and prepared with the help of computer-aided design (CAD) and computer-aided manufacturing (CAM) software. One thousand and zero millimeters in length, three hundred and twenty millimeters in width, and twelve hundred and sixty millimeters in height describe this machine for chopping up plastic trash. In terms of crushing time and capacity, variations in the rotational speed of 1000, 1100, and 1200 blades in revolution per minute were optimal. The optimal crushing time for 2 kg-HDPE plastic waste was 37 seconds at 1200 revolutions per minute, followed by 1100 revolutions per minute; 2 kg-HDPE plastic waste was crushed and evaluated. HDPE plastic wastes have typically crushed faster in less time than PET plastic wastes. It has been evaluated and validated for any setting variation operation involving the crushing speed. Three kilograms of HDPE plastic waste yielded an optimum crushing capacity of 194.4 kg/hour at 1200 revolutions per minute. Next, at 1200 revolutions per minute, 2 kg-HDPE plastic waste is crushed. HDPE plastic wastes are typically more effective to crush than PET plastic wastes, regardless of the crushing speed setting variation operations. As a result of this study, plastic waste is being put to better use, helping to cut down on overall plastic use in the plastic waste management